2019
DOI: 10.3906/bot-1807-80
|View full text |Cite
|
Sign up to set email alerts
|

Use of hydrogen peroxide in acclimation of basil (Ocimum basilicum L.) to salt stress

Abstract: The aim of this study was to verify the effects of application of H 2 O 2 on salt tolerance and oil production in basil cv. 'Gennaro de Menta' grown in a hydroponic system. Seedlings were subjected to 3 levels of H 2 O 2 (0, 1, and 1000 μM) in a nutrient solution during 2 different exposure periods (24 and 48 h) and 2 levels of NaCl (0 and 80 mM). The plants were harvested at preflowering (at 15 days) and postflowering (at 25 days). At 25 days, the application of 1 μM H 2 O 2 /48 h and its reapplication at pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…In contrast, the increase observed at 35 days, in H 2 O 2 -primed plants may be because the chloroplast protein associated with chlorophyll is unexcited, facilitating the process of chlorophyll extraction under salt stress conditions (Liang et al, 2018). Cova et al (2019) and Silva et al (2019) also found that salinity increased the Chl a content in noni (Morinda citrifolia) and basil (Ocimum basilicum) plants, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, the increase observed at 35 days, in H 2 O 2 -primed plants may be because the chloroplast protein associated with chlorophyll is unexcited, facilitating the process of chlorophyll extraction under salt stress conditions (Liang et al, 2018). Cova et al (2019) and Silva et al (2019) also found that salinity increased the Chl a content in noni (Morinda citrifolia) and basil (Ocimum basilicum) plants, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…As a consequence of this mechanism, there is also an increase in SUC, which is a variable that indicates the amount of water per unit leaf area. Some authors claim that the increase in SUC, besides maintaining water storage, can be an important mechanism for diluting toxic ions (Cova et al, 2016;Silva et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conforme Bione et al (2014) (SANTOS et al, 2019;SILVA et al, 2019), as plantas foram espaçadas nos canais hidropônicos em 0,25; 0,30 e 0,10 m, respectivamente.…”
Section: Introductionunclassified